The field class in the teaching of geography: daily life experiences in the city to build learning - de Jesus, Myrian Cristina Santos; Santos, Mateus Ferreira (Revista Ensino de Geografia (Recife), 2019)
This article presents contributions about the field class in basic geography teaching, pointing out methodological paths that can be adopted by teachers of the city of basic education. It is necessary to understand the changes taking place in society, making it essential for understanding and building the spatial knowledge, and encourage the exercise of citizenship. The teaching of Geography, as a body of knowledge that allow sociability, should be able to propose to the student recognition of the city as a stage of learning. The city and its phenomena need to have space in the classroom, in orderto drive the student to be recognized as the subject of this space, not passively, but as a citizen and transforming agent. For this, it made a bibliographic nature of research in order to dialogue with authors who discuss the teaching of geography and field class with different methodological possibilities that can be used by teachers of public and private , willing to promote their students a dynamic teaching, interactive and reflective, whose theory can be experienced during the field school